2004
DOI: 10.1002/hep.20078
|View full text |Cite
|
Sign up to set email alerts
|

Structured treatment interruption in patients with alveolar echinococcosis

Abstract: In human alveolar echinococcosis (AE), benzimidazoles are given throughout life because they are only parasitostatic. It has been a longstanding goal to limit treatment, and recent reports suggest that, in selected cases, benzimidazoles may be parasitocidal. Previously, we showed that positron -emission tomography (PET) using [ 18 F]fluoro-deoxyglucose discriminates active from inactive lesions in AE. We have now performed a 3-year prospective study in 23 patients and conducted a structured treatment interrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
132
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 28 publications
1
132
3
2
Order By: Relevance
“…PET/CT cannot explain the viability of the parasite directly and a negative study does not mean the death of the parasites completely. However, it can reliably evaluate the inflammatory response and can show the parasitic activity indirectly (40). Therefore, it is the most accepted imaging modality in adjusting the primary therapy, the longterm benzimidazole therapy in inoperable patients, and in follow-up of the patients (12, 13, 40).…”
Section: Pet-ctmentioning
confidence: 99%
See 1 more Smart Citation
“…PET/CT cannot explain the viability of the parasite directly and a negative study does not mean the death of the parasites completely. However, it can reliably evaluate the inflammatory response and can show the parasitic activity indirectly (40). Therefore, it is the most accepted imaging modality in adjusting the primary therapy, the longterm benzimidazole therapy in inoperable patients, and in follow-up of the patients (12, 13, 40).…”
Section: Pet-ctmentioning
confidence: 99%
“…Benzimidazoles (mebendazole and albendazole) are parasitostatic drugs that can be used against parasitic metacestodes (2,12,16). Although benzimidazoles are widely regarded as parasitostatic, it has been reported that they may, in some cases, exert parasiticidal effect and thus the treatment may be safely terminated after some time (37,40). On the other hand, these drugs have some side effects and are potentially teratogenic.…”
Section: Treatment and The Role Of Interventional Radiologymentioning
confidence: 99%
“…For alveolar echinococcosis, these compounds were shown to act parasitostatically rather than parasitocidally, with high recurrence rates after interruption of therapy. Improved drug treatments are needed (8,24).Most countries to which malaria is endemic have now adopted artemisinin-based combination therapy as a first-line treatment for Plasmodium falciparum infection (34), and activities of artemisinins against other protozoans have been reported (1, 12). Trematodes, including schistosomes (31) and others, have proven susceptible to artemisinins and semisynthetic derivatives (13)(14)(15)(16)26), and antitumor activities of artemisinins have been reported (11,18,35).…”
mentioning
confidence: 99%
“…Severe side effects may be observed, and the parasitostatic effect of these drugs implies that E. multilocularis is not depleted and may resume growth after discontinuation of treatment (3,18). The overall success rate of benzimidazole treatment ranges between 55 and 97% (4,9,19).…”
mentioning
confidence: 99%